Modulatory effect of Echium plantagineum oil on the n-3 LC-PUFA biosynthetic capacity of chicken (Gallus gallus) - Jesús Villora; José Antonio Pérez; Nieves Guadalupe Acosta; Deiene Rodríguez-Barreto; Pedro Juan Alonso; Mónica B. Betancor; Alexandr Torres; Sergio Álvarez; Covadonga Rodríguez (Poultry Science)
Poultry can be a sustainable source of eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) through the bioconversion of dietary alpha-linolenic acid (ALA, 18:3n-3). However, this process is currently limited by the high n-6/n-3 ratio in poultry diets affecting the competition between n-6 and n-3 fatty acids (FA) for the same biosynthetic enzymes, and the rate-limiting Δ6 desaturase which act at both, the first and final steps of DHA synthesis pathway. Echium plantagineum oil (EO) is an unusual source of stearidonic acid (SDA, 18:4n-3) which bypasses the first Δ6 desaturase step potentially increasing n-3 long-chain polyunsaturated fatty acids (LC-PUFA) synthesis. To explore this hypothesis, 60 Canarian male chickens at 18 weeks of age were divided into three groups and fed diets differing only in their FA formulation: soy oil (SO) rich in linoleic acid (LA, 18:2n-6); linseed oil (LO) rich in ALA; and EO, a balanced LA/ALA oil also rich in SDA and γ-linolenic acid (GLA, 18:3n-6). The dietary treatments did not affect the total lipid (TL) content (p>0.05) and did not substantially vary the lipid class (LC) profiles in the brain, liver, intestine, and muscle tissues. However, the inclusion of LO and EO equally increased n-3 polyunsaturated fatty acids (PUFA) levels in the brain, liver, and intestine compared to animals fed with SO (p<0.05). Moreover, EO increased hepatic relative expressions of the fatty acid elongases (elovl2 and elovl5). Consequently, and in alignment with our hypothesis, EO was more effective than LO in enriching chicken thigh meat with n-3 LC-PUFA (6.0 vs 4.2%; p<0.05). We concluded that lowering the dietary LA/ALA ratio and increasing the SDA content in poultry diets enhance the potential of chicken metabolism for enriching poultry products with n-3 LC-PUFA. Emerging evidence suggest that local plants like those including in Echium genus, rich in SDA and with a balanced LA/ALA ratio, could offer a more sustainable and efficient alternative to traditional ALA sources in poultry production.